THE FAMILY KNOWLEDGE AND THE RECURRENCE OF SCHIZOPHRENIC PATIENTS - Arni Nur Rahmawati; Maryanto Maryanto; Apriliyani Ita (Indonesian Journal of Community Health Nursing, 2022)
Introduction: Schizophrenia is a type of high-level disorder that has behaviors such as aggressive and often screaming hysterically. This mental health often experiences recurrences after being hospitalized because it has entered the most severe type of disorder. Families whose family members have schizophrenia need to know about the treatment of schizophrenic patients. The purpose of the study was to describe between the level of family knowledge and the recurrence rate of schizophrenic patients at the Pekuncen 1 Health Center, Banyumas Regency. Method: Descriptive study research design with cross- sectional time approach. The samples in this study were families of schizophrenic patients in the work area of the Pekuncen Health Center 1 Pekuncen District, Banyumas Regency totaling 60 people with a total sampling technique. The research instrument uses a questionnaire. Data analysis using spearman-rank test. Results: The results showed that the family knowledge of schizophrenic patients in the category was sufficient (50%). The recurrence rate of schizophrenic patients is in the high category (60%). The results of the spearman rank correlation test obtained the results of a p-value of 0.0001 and a rho value of -0.453. Conclusion: The conclusion is that there is a moderate and negative relationship between the level of family knowledge and the level of recurrence of schizophrenic patients at the Pekuncen 1 Health Center, Banyumas Regency.   Keywords: knowledge; recurrence; schizophrenia